Óleos vegetais obtidos por extração mecânica em rações para tilápia do Nilo: desempenho e quantificação de ácidos graxos - Higuchi, Leticia Hayashi (2010)
The aim of this study was evaluate the inclusion of different vegetable oils obtained by mechanical extraction in the feeding of Nile tilapia (Orechromis niloticus). The first study evaluate the performance and hundredth composition of Nile tilapia were aimed. We conducted the experiment at the Laboratory Cultivation of Aquatic Organisms from Research Group GEMAq/Unioeste with 320 Nile tilapia with initial weight and initial medium total length of 2.55 ± 0.57 g and 5.59 ± 0.43 cm, respectively. The treatments included oils of (sunflower, canola, sesame, linseed, peanut, nut of Pará, soy and macadamia nuts) with an addition of 4%, with diets containing 32% crude protein and 3500 kcal/kg energy digestible. Was valued the weight gain (GP), total length (CT), feed conversion apparent (CAA), diet consumption (CR) and survival (SO). There was no significant difference (P> 0.05) between the performance variables. However, distinctions can be observed (P <0.05) on water content, crude protein and total lipid to the hundredth composition after 30 and 60 days of experiment. In the second study, the objective was to evaluate the quantification on fatty acids in lipids of tilapia fingerlings. The major fatty acids (mg/g total lipids (LT)) were oleic, palmitic, linoleic and linolenic. The sum of fatty acids polyunsaturated after 60 days of culture showed an increase in all treatments compared with 30 days of experiment. This is due to the addition of oils with high contents of fatty acids n-6 and n-3 in the diet. In conclusion it is recommended to use linseed oil as feed for tilapia fingerlings, due to the great improvement in the ratio of n-6/n-3.